OUTPUT AND UNEMPLOYMENT: TESTING OKUNâS LAW IN INDONESIA - Yaumidin, Umi Karomah (RIEBS, 2015)
This paper reports a study of the testing of Okunâs Law in the Indonesian economy: we test difference and gap models of Okunâs thesis. For this we use annual data on GDP and unemployment rates for Indonesia from 1980 to 2013. The main conclusions are, first, that Indonesia still faces a continuing high unemployment rate according to the results of the output gap model and of the first difference model. Second, in the long term, demand in Indonesiaâs employment market is inelastic, especially during financial crises. Indonesia needs high economic growth to cause demand for labour to be more elastic to absorb many more into the labour force. Overall, our analyses found that interpretations of Okunâs Law might not be applicable to Indonesiaâs economy.